Water technology in the Middle Ages : cities, monasteries, and waterworks after the Roman Empire - Magnusson, Roberta J., 1952- (Johns Hopkins studies in the history of technology., 2001)
Focusing attention on gravity-fed water-flow systems in mediaeval cities and monasteries, Roberta J. Magnusson challenges the view that hydraulic engineering died with the Romans and remained moribund until the Renaissance.